(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
The experiment was conducted to develop the chocolate-flavored soy dahi and find the accepted level of soymilk that should be added to milk to produce chocolate-flavored dahi. Therefore, four distinct kinds of dahi designated T0 (control, 100% cow milk), T1 (75% cow milk and 25% soy milk) and T2 (50% cow milk and 50% soy milk) and T3 (25% cow milk and 75% soy milk) were prepared by partially substituting cow milk to soy milk. Each variety also contained 1.5% cocoa powder. A panel of professional judges assessed the sensory (organoleptic) properties of the produced samples. The physical study’s findings revealed that the overall organoleptic (i.e., smell and taste, body and texture, color and appearance) scores of dahi of kinds T0, T1, T2, and T3 varied significantly (P<0.01) from one another. According to the findings of the chemical test, the soy milk addition considerably lowered the amount of fat, acidity, total solids, and minerals while dramatically increasing the amount of moisture and protein (P<0.05). The growth of lactic acid bacteria is considerably better, however, it gradually reduces with the higher Addition of soy milk to cow milk. Based on the findings, it was concluded that soy milk could substitute milk by 25%, producing dahi that may be almost as good as that made only with milk and cocoa powder. Asian Australas. J. Biosci. Biotechnol. 2023, 8 (1), 1-7